Development of a Project-Based Learning Model in a Learning Management System using an Iterative Incremental Approach - Rice Novita; Medyantiwi Rahmawita M; Raudah Islamiah (Journal of Innovation and Technology Polbeng Series on Informatics (INOVTEK Polbeng - Seri Informatika), 2025)
Technological innovation in education has driven the adoption of Learning Management Systems (LMS) as a primary platform for digital learning. However, current LMS implementations remain focused on knowledge transfer and have not fully supported Project-Based Learning (PjBL), a model that emphasizes active learner engagement in producing concrete outputs. This study aims to develop a project-based learning model within a learning management system using an iterative incremental approach in the software engineering course. The development method refers to the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation) to design project-based learning syntax, which is then integrated into the LMS using the iterative incremental approach and system design based on Object-Oriented Analysis and Design (OOAD). The resulting product consists of a project-based learning module and web-based learning media, both validated by education and information technology experts. Validation results show that the learning module obtained a validity score of 0.83, while the learning media (LMS) obtained a score of 0.84, both categorized as valid. These findings indicate that the initial design of the PjBL-integrated LMS aligns with pedagogical and technical requirements, although its effectiveness and practicality have not yet been tested and remain areas for further research. The contribution of this study lies in integrating RPL-specific PjBL syntax into LMS features developed using the iterative incremental model, providing a foundation for more adaptive and collaborative PjBL-oriented LMS development in digital learning.